2020
DOI: 10.1007/s11136-020-02527-0
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de Vida: a systematic review of quality of life in Latino cancer survivors in the USA

Abstract: Background-Cancer is the leading cause of death among Hispanics/Latinos. Thus, understanding health-related quality of life (HRQOL) needs among this diverse racial/ethnic group is critical. Using Ferrell's multidimensional framework for measuring QOL, we synthesized evidence on HRQOL needs among Hispanic/Latino cancer survivors.Methods-We searched MEDLINE/PubMed, EMBASE, CINAHL, and PsycINFO, for English language articles published between 1995 and January 2020, reporting HRQOL among Hispanic/ Latino cancer su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 174 publications
(323 reference statements)
1
22
0
Order By: Relevance
“…This is concerning given that Latino and Asian/Pacific Islander lung cancer survivors have previously reported a greater number of unmet supportive care needs than their White counterparts 57 and a systematic review found quality-of-life outcomes among Hispanic/Latino cancer survivors to be worse than any other racial/ethnic group. 58 Our findings that lung cancer survivors were screened at higher rates than ovarian cancer survivors could reflect that some CoCaccredited facilities focus screening efforts on the most common cancer diagnoses at their facilities. Our study also found that survivors with more advanced disease got screened at higher rates than those with an earlier disease stage.…”
Section: Discussionmentioning
confidence: 80%
“…This is concerning given that Latino and Asian/Pacific Islander lung cancer survivors have previously reported a greater number of unmet supportive care needs than their White counterparts 57 and a systematic review found quality-of-life outcomes among Hispanic/Latino cancer survivors to be worse than any other racial/ethnic group. 58 Our findings that lung cancer survivors were screened at higher rates than ovarian cancer survivors could reflect that some CoCaccredited facilities focus screening efforts on the most common cancer diagnoses at their facilities. Our study also found that survivors with more advanced disease got screened at higher rates than those with an earlier disease stage.…”
Section: Discussionmentioning
confidence: 80%
“…45 A meta-analysis and systematic review found that Latinx patients with cancer show worse distress, depression and overall health-related quality of life (HRQOL) than other minority patients and whites. 46 Similarly, Latinx patients report higher levels of burden, depression and physical health problems than patients of other ethnicities. 47 48 Therefore, addressing family issues is crucial in the adjustment and well-being of Latinx with advanced cancer and their informal caregivers.…”
Section: Introduction Patients With Advanced Cancer and Informal Care...mentioning
confidence: 99%
“…Adapting and developing culturally sensitive interventions is needed for Latinx families coping with advanced cancer (stage III or IV) [ 1 , 2 , 3 ]. Latinx patients coping with cancer have reported the need to include cultural values such as family and spirituality [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%